Study ability of protection effect of organic acids for multi-metallic anti-corrosion additive system in ethylene glycol-water coolants - Pham Thi Mai Huong,; Nguyen Thi Huong, (Vietnam Journal of Science and Technology, 2024)
In this work, the electrochemical behavior of carbon steel, brass, bronze and aluminum alloys in the presence of various important organic acids (sebacic acid (SbA), terephthalic (TPA), 2-ethylhexanoic (E2C6A), and octanoic (C8A)) and the effect that these have on the growth and protectiveness of the alloys have been investigated. The results show that the presence of organic acids in the coolant increases the protective effect of the system by forming a film on the surface of the alloys. The EIS impedance results demonstrate the formation of active and passive protective layers on the surface of the alloys. The results of surveying 04 types of organic acids for the protection of different alloy substrates show that TPA and SbA acid additives are more effective than C8A and E2C5A. The additive C8A not only did not inhibit corrosion but also promoted this process strongly, especially with aluminum alloys and the TPA has the best anti-corrosion effect for steel, followed by C1 copper alloy and aluminum.